TI_GERICHTE 11.2010.107 vom 9. Oktober 2012 , Cancellazione di servitù: impossibilità giuridica di esercitare un passo veicolare - TI Tribunale d'appello (2012)
Cancellazione di servitù: impossibilità giuridica di esercitare un passo veicolare